Conflict, extremism, resilience and peace in South Asia; can covid-19 provide a bridge for peace and rapprochement? - Bhutta, Zulfiqar A.; Mitra, Arun; Salman, Afsah; Akbari, Fawad; Dalil, Suraya; Menon, Purnima (BMJ, 2021)
South Asia, home to 1.97 billion people (25% of the world’s population), is no stranger to conflict and confrontation. Longstanding border disputes (such as between India and China and the decades-old standoff between India and Pakistan), the forced displacement of Myanmar Muslims to Bangladesh, and the 2021 rise of the Taliban triggering a mass exodus of professionals and educated women from Afghanistan underscore the enormous volatility and unpredictability of the region. Climate change poses a further challenge, with the real risk of interstate “water wars.”1 Indeed, South Asia now faces a range of threats, with real risks of these spilling over into interstate conflict. The links between longstanding conflict, insecurity, and poverty are well recognised.23 Abject poverty, especially when associated with disparities, underlies many of the known conflicts worldwide, unsurprisingly given the drain conflict places on social sector spending. And although lack of social inclusion and ethnic inequalities have been shown to lead to domestic terrorism,4 economic inequalities and grievances are stronger drivers of rebellion,5 and are particularly relevant in South Asia. Despite robust economic growth and progress on many technological fronts, South Asia still has the world’s largest concentrations of poverty, illiteracy, malnutrition, and preventable maternal and child deaths outside sub-Saharan Africa.6 Widespread poverty is closely intertwined with social disparities, marginalisation on the basis of an egregious caste system, and vast inequities that perpetuate disillusionment, grassroot rebellion, and further conflict.